“BILIK LAKTASI” UNIB: SEBUAH BENTUK DUKUNGAN TEMPAT KERJA TERHADAP SUKSES IBU PEKERJA MENYUSUI - Siti Aisyah; Sularsih Anggarawati; Sura Menda Ginting; Halimatusyadiah Halimatusyadiah (Universitas Bengkulu, 2018)
According to Permenkes RI nomor 15 tahun 2013 on How Providing the Special Facility for Breastfeeding and or breast milk, Lactation Room or Nursing Room is a special room equipped with facilities for breastfeeding directly to the baby or breast milk and keep the milk, and or a counseling room for breastfeeding. Availability of lactation room is increased the positive image of University of Bengkulu in level of local, national, and international community as one of efforts to reach the quality of world class university. University of Bengkulu should be the pioneer of such this program in Bengkulu Province. Lactation room, called Bilik Laktasi, is 4.5 m x 8.5 m’s room that accommodate of maximum of 10 infants and breastfeeding mothers. This room is equipped with mattresses and toys, a refrigerator, cooling box, fan, dispenser, and other supporting facilities. A trained nanny will manage the room and standard operational procedurals are set for services. Keywords: Lactation Room, Breastfeedind, breastfeeding milk, working women, employer